Creep and residual properties of cracked macro-synthetic fibre reinforced concretes - Serna Ros, Pedro (2016)
This study analysed the creep behaviour of five concretes incorporating 0·5% by volume of four macro-synthetic fibres (MSFs) and one steel fibre. After 28 d moist curing, prisms were pre-loaded up to a crack opening of 0·5 mm and held for 90 d in three different environments - ambient laboratory air, seawater at 45°C and air flow at 45°C. Sustained loads were then applied on three specimens from each group while the other prisms remained unloaded. The remaining residual capacity was evaluated by bending tests. It was concluded that the residual capacity of cracked MSF concretes is not affected by long-term loading.